2017
DOI: 10.1523/eneuro.0013-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

Neurochemical Heterogeneity Among Lateral Hypothalamic Hypocretin/Orexin and Melanin-Concentrating Hormone Neurons Identified Through Single-Cell Gene Expression Analysis

Abstract: The lateral hypothalamic area (LHA) lies at the intersection of multiple neural and humoral systems and orchestrates fundamental aspects of behavior. Two neuronal cell types found in the LHA are defined by their expression of hypocretin/orexin (Hcrt/Ox) and melanin-concentrating hormone (MCH) and are both important regulators of arousal, feeding, and metabolism. Conflicting evidence suggests that these cell populations have a more complex signaling repertoire than previously appreciated, particularly in regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
105
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(118 citation statements)
references
References 134 publications
7
105
0
6
Order By: Relevance
“…Importantly, most MCH neurons express only Vglut2, but not other vesicular glutamate transporters viz. Vglut1 or Vglut3 (only a very small percentage of MCH neurons express Vglut3) (Mickelsen et al 2017) and therefore loss of Vglut2 was expected to completely abolish glutamate release from these neurons.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, most MCH neurons express only Vglut2, but not other vesicular glutamate transporters viz. Vglut1 or Vglut3 (only a very small percentage of MCH neurons express Vglut3) (Mickelsen et al 2017) and therefore loss of Vglut2 was expected to completely abolish glutamate release from these neurons.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, we recently found that MCH neurons may not contain vesicular GABA transporter (Vgat) necessary for packaging GABA into the vesicles for synaptic release (Chee et al 2015a). While vesicular monoamine transporters (VMAT 1 and 2) can mediate GABAergic neurotransmission, MCH neurons are also devoid of these transporters (Mickelsen et al 2017). Consistent with this, optogenetic stimulation of MCH neurons did not release GABA in the lateral septum, the brain region that receives the densest MCH projections (Chee et al 2015a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eberwine et al (1992) [98] performed gene expression analysis on individual, freshly dissociated hippocampal neurons. More recently, single-cell isolation has now been conducted using laser-capture microdissection (LCM) methods; e.g., [37, 47, 56, 239, 456], or cell sorting methods (e.g., [64, 69, 95; 160; 264; 278; 368]; also see [312, 351]). Thus, single cell isolation methods first used for the purposes of morphological and structural investigation evolved for use in biochemical, molecular and functional analyses.…”
Section: Historical Antecedentsmentioning
confidence: 99%
“…The Jackson laboratory has recently reported single-cell transcriptomic data obtained from LHA H/O-expressing neurons and MCH-expressing neurons in mouse transgenic lines [278]. Importantly, in their study, they show specific delineations of the regions they dissected using atlas-based coordinates and drawings of the estimated areas they micropunched.…”
Section: Molecular Mining Of the Hypothalamusmentioning
confidence: 99%